Decentralization in Malaysia’s Zakat Management Organizations: A Comparison of Some States’ Zakat Collection Achievements - Muhsin Nor Paizin (Center of Strategic Studies (PUSKAS) BAZNAS, 2022)
The federal constitution defines Malaysia as a constitutional monarchy. The division of powers between the federal and state governments in the two lists has been explained by referencing the Federal Constitution’s Ninth Schedule. The federal government’s State List-II (aka the Federal List) gives significant control over various Muslim practices, such as zakat, and Malay tradition, to the states. So, therefore, it falls under the jurisdiction of the states to administer zakat. There are state-run zakat management organizations where decentralization has been implemented. This study aims to find out if decentralized zakat management, based on the findings of five Malaysian states: Johor, Perak, Selangor, Penang, and the Federal Territory, has a significant impact on overall zakat collection in the country. A significant benefit of decentralizing zakat collection efforts is that those efforts are more likely to produce better results. Collecting zakat using advanced channels provides a benefit in terms of various aspects of the collection system, and this represents a new stage in zakat collection when compared to economic data.